The role of Islamic Corporate Social Responsibility in building corporate image to increase customer loyalty - Irmayanti Hasan; Lailatul Farida; Kholilah Kholilah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
This research aims to determine the influence of Islamic Corporate Social Responsibility and Corporate Image on Customer Loyalty. The research was conducted by sending questionnaires to sharia banking customers in Malang. There were 100 respondents to the study. This research is quantitative. The analysis technique used is Partial Least Square. The results showed that Islamic Corporate Social Responsibility affects Corporate Image and Customer Loyalty. This study successfully proved that CSR activities carried out by Sharia banking can increase customers' trust in Sharia banking. Besides, the survey results also showed that corporate image could not mediate ICSR's influence on customer loyalty because many customers do not know CSR activities done by Sharia banking. This study's limitations were question items in the questionnaire that did not pass the validity and reality test and a relatively small number of respondents. Further research can use question items that better describe the variables used, and analysis can be done on sharia banking customers throughout Indonesia so that the results can be more generalized.